Local vs. foreign made : are Malaysian etnocentric? - Bojei, Jamil; Alwie , Aryaty; Awang Tuah, Siti Normah; Ahmad, Maisarah (2010)
The purpose of this study is to examine the effect of consumer ethnocentrism on attitudes toward foreign products among consumers in Malaysia. Self-administered questionnaires were developed and distributed based on convenient sampling. Measures were adopted from previous literatures. The higher the consumer ethnocentric tendencies are, the more reluctant they are to purchase foreign products. Consumers who are high in ethnocentric tendencies show less sense of global openness. This study contributes towards the consumer ethnocentrism literature as the findings did concur with findings from western samples. As reflected in the Malaysian consumers’ sample, strong ethnocentric sense was accounted for but traded off by the lack of sense of global openness.